A Comparative In Vivo and In Vitro Study on the Effectiveness of Homoeopathic Medicines on Aquarium Zebrafish Infected with Vibrio parahaemolyticus - Aiswarya, A.S.; Reshmy, K.R.; Chandraja, C.V.; Sisir, P.R. (Homœopathic Links, 2020)
Background Human infections associated with Vibrio parahaemolyticus rank high among the pathogenic bacteria associated with fishes which causes septicaemia and gastroenteritis in humans. Humans acquire such infections by handling of infected fishes. Therefore, rather than curing the diseases in humans, it can be prevented in fishes by homoeopathic medicines.Objectives The main objective of the study is to show the effectiveness of homoeopathic medicines in curing aquarium zebrafish infected with Vibrio parahaemolyticus.Materials and Methods Fifteen pairs of healthy aquarium zebrafish were chosen for the study. They were inoculated with Vibrio parahaemolyticus after the acclimatisation period of 1 month. The signs were noted down in chronological order. homoeopathic medicines Sulphur 200, Arsenicum album 200 and Pyrogenium 200 was administered based on the totality obtained. An in vitro study was also done by the serial dilution of water from each tank and also by the serial dilution of the fish gut which was plated in thiosulphate-citrate-bile salts-sucrose (TCBS) agar media. A growth sensitivity study to show the growth inhibition was done on Muller Hinton agar media.Results Although the incubation period of vibriosis was 4 days, the condition was completely cured within 10 days of administration of homoeopathic medicines. But in the case of tetracycline, the signs disappeared after 15 days. Sulphur being deep acting remedy showed cure in fishes as well as in the water. Arsenicum album showed therapeutic as well as prophylactic characters.Conclusion From the study, it is proved that the Sulphur 200 was the most effective remedy. Homoeopathic medicines do not produce any resistant bacteria but improves the immunity of the living organism. Sulphur, the deep acting remedy ensures 100% cure, i.e., both the water and the fishes are cured of Vibrio parahaemolyticus.
Keywords: Arsenicum album 200; Danio rerio; in vitro; in vivo; Pyrogen 200; Sulphur 200; Vibrio parahaemolyticus